Emergency Radiology of the Chest and Cardiovascular System - Scaglione, Mariano; Linsenmaier, Ulrich; Schueller, Gerd; Berger, Ferco; Wirth, Stefan (Medical Radiology,, 2017)
This book provides an up-to-date, systematic review of all facets of emergency radiology in patients with chest trauma or pain with the aim of equipping the reader with a detailed knowledge of the various radiological patterns, which is essential in order to make a prompt diagnosis under circumstances when time is of critical importance. To this end, the indications, value, and results of the various emergency imaging modalities, including sonography and interventional radiology, are described and illustrated in the full range of blunt chest injuries and nontraumatic chest emergencies. Technological aspects, protocols tailored to the mechanism of injury, and post-processing techniques are also extensively covered. Emergency Radiology of the Chest and Cardiovascular System will be of value to general and interventional radiologists, radiology residents, radiology technicians, and all physicians and surgeons who work in emergency care.